Older Drivers' Experience With Automated Vehicle Technology: Interim Analysis of a Demonstration Study - Classen, Sherrilene; Mason, Justin; Wersal, James; Sisiopiku, Virginia; Rogers, Jason (Frontiers in Sustainable Cities, 2020)
Older adults (> 65 years) account for 20% of the US population but are over-represented in multiple-vehicle crashes. Automated vehicles (AVs) may hold safety benefits for older drivers, if they adopt this emerging technology. Therefore, this study is using a randomized, crossover design with pre- and post-exposure surveys, to quantify older drivers’ perceptions, who were exposed to a simulator running in automated mode and riding in a highly automated shuttle (SAE Level 4). An interim analysis (N=69) compares older drivers’ perceptions before and after exposure to the automated simulator and automated shuttle. Early findings indicate that exposure to AV technology may positively affect older adults’ perceptions to this emerging technology. In this study, older drivers’ trust and perceived safety increased after being exposed to the driving simulator or automated shuttle compared to baseline. Older drivers’ perceptions of perceived usefulness and cost of AVs, increased after being exposed to both modes of vehicle automation compared to baseline whereas their perceptions did not change after their first AV exposure (regardless of it was the simulator or shuttle). Exposing older adults to an automated simulator or on-road automated shuttle may promote older adults’ acceptance and adoption of AVs.